2010
DOI: 10.1001/archoto.2010.168
|View full text |Cite
|
Sign up to set email alerts
|

Current Techniques in Management of Postmeningitic Deafness in Children

Abstract: Pneumococcal vaccination has reduced but not eliminated childhood deafness secondary to pneumococcal disease. Auditory steady-state response testing and 3-dimensional steady-state free precession imaging are modalities that expedite candidacy evaluation of this population. Early bilateral simultaneous implantation increases the likelihood of binaural hearing and ensures implantation of the better ear in this population of children whose course is often complicated by formation of scar tissue and ossification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Almost all bacteria species causing meningitis have been associated with permanent postmeningitic hearing loss, but this complication is most frequently found in S. pneumoniae, N. meningitides, and H. Influenza infections [6, 15, 16]. The prevalence of meningitis caused by these bacteria has decreased after the implementation of vaccination programmes in western countries [15, 17, 18]. The patients described in the current study also received vaccines against S. pneumoniae, N. meningitides, and H. Influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all bacteria species causing meningitis have been associated with permanent postmeningitic hearing loss, but this complication is most frequently found in S. pneumoniae, N. meningitides, and H. Influenza infections [6, 15, 16]. The prevalence of meningitis caused by these bacteria has decreased after the implementation of vaccination programmes in western countries [15, 17, 18]. The patients described in the current study also received vaccines against S. pneumoniae, N. meningitides, and H. Influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging assessment of labyrinthitis ossificans is essential for surgical planning because these patients benefit from urgent referral for evaluation and cochlear implantation before obstruction of the cochlea occurs (37). Early implantation before the onset of substantial obstruction is necessary to achieve optimal electrode insertion and avoid the need for complex alternative surgical approaches, which have more variable outcomes.…”
Section: Cochlear Patencymentioning
confidence: 99%
“…Also, the role of time between PMD and implantation is arguable. Some survey recommended that CI should be performed after diagnosis of PMD as soon as possible and other suggested late approach (14).Young et al showed that early bilateral simultaneous CI in children with PMD increases the likelihood of binaural hearing and ensures implantation of the better ear in this population of children whose course is often complicated by formation of scar tissue and ossification within the cochlea (15). Regarding to the results of present study and similar studied we conclude that children with post meningitis deafness could be Benefited from CI.…”
Section: Dear Editormentioning
confidence: 99%